Subacute Sclerosing Panencephalitis: Recent Advances in Pathogenesis, Diagnosis, and Treatment - Ravindra Kumar Garg; Shweta Pandey (Annals of Indian Academy of Neurology)
Subacute sclerosing panencephalitis (SSPE) is a relentless progressive brain disorder caused by the persistent presence of mutated measles virus in the central nervous system. The disease typically develops years after primary measles infection, with the highest risk observed in children infected before the age of 2 years. The global incidence of SSPE is notably higher in low- and middle-income countries and in regions with low measles vaccination coverage. The pathogenesis of SSPE involves viral persistence through mutations in viral proteins, enabling immune evasion and cell-to-cell propagation within the brain. Neuroinflammation, immune-mediated damage, and neuronal loss further contribute to disease progression. Clinical manifestations range from progressive cognitive decline and behavioral changes, along with myoclonus, seizures, movement disorders, visual impairment, and, finally, a vegetative state. Diagnosis is confirmed through cerebrospinal fluid analysis showing elevated antimeasles antibodies, characteristic periodic electroencephalography discharges, and neuroimaging findings like white matter hyperintensities and cerebral atrophy. Treatment remains challenging, with isoprinosine, interferon-α, ribavirin, and newer agents like favipiravir and aprepitant offering new hope. Symptomatic management and palliative care are needed in all patients. SSPE is invariably fatal. Notably, reports of prolonged survival and disease stabilization have been documented, particularly with early and combined therapy. The coronavirus disease 2019 pandemic’s adverse impact on measles vaccination rates highlights the urgent need for robust measles immunization campaigns. Future directions involve exploring antiviral fusion peptide inhibitors and artificial intelligence-driven diagnostic tools to improve early detection, treatment efficacy, and outcome prediction in SSPE.